DEFECTIVE HUMAN IMMUNO‐DEFICIENCY VIRUS (HIV) PARTICLES PRODUCED BY CLONED CELLS OF HTLV‐I‐CARRYING MT‐4 CELLS PERSISTENTLY INFECTED WITH HIV - Ikuta, Kazuyoshi (Jpn J Cancer Res, 1988)
Persistently HIV‐infected cell lines were isolated from surviving and proliferating cells after infection of HTLV‐I‐carrying MT‐4 cells with cell‐free human immunodeficiency virus (HIV); HTLV‐IIIB and LAV. The media of the cloned cell cultures did not cause HIV infection of MT‐4, MOLT‐4, TALL‐1, or HL‐60 cells. Most of the constituents of the virus in the media were env proteins and many defective doughnut‐shaped particles released from the cells were identified by electron microscopy.